Psychosocial outcomes after young age onset cancer - Ahomäki, Ritva (fi=Turun yliopisto|en=University of Turku|, 2018)
Background: Since the number of childhood and adolescent/young adult (AYA) cancer survivors is increasing due to improved survival rates, the incidence of cancer associated late-effects has also increased. Cancer survivors need to receive structured and supportive follow-up. Aims and methods: In order to reveal the psychosocial outcomes of childhood and AYA cancer survivors, four national, registry-based studies were conducted. In the first study, educational and social outcomes of childhood cancer survivors were examined in comparison with age-matched population controls. The following study aimed to determine, whether the modifications made to the acceptance guidelines of military service have altered childhood cancer survivors’ enlistment rates, and how well the enlisted survivors perform in the physical fitness and cognitive tests as compared to healthy controls. In two studies, psychiatric outcomes of childhood and young adult cancer patients were examined by assessing Hospital Discharge Register and Drug Purchase Register to determine late psychiatric morbidity as well as and frequencies of antidepressant purchases by cancer patients as compared to siblings. Results: There was an elevated proportion of survivors with no further education after comprehensive school in all three main diagnostic groups (brain tumors (BT), solid tumors (ST), leukemias/non-Hodgkin lymphomas (NHL). However, the risk for unemployment was not increased, but early retirement was more common in comparison to the general population. The exemption rate from military service of cancer survivors was found to be significantly higher than that of population controls, but in general terms, the enlisted survivors coped well with their military training. It was found in study III that, the risk for organic memory/brain disorder was higher in cancer survivors in both age groups (0-19 and 20-34 years at diagnosis) than in their siblings and elevated HRs for mood disorders were found in females (both age groups). In addition, higher frequencies of antidepressant purchases were also detected in females in both age groups. Conclusions: Childhood BT and leukemia/NHL survivors seem to require special educational support after their cancer treatments, and since childhood cancer survivors are at risk for premature retirement, adequate social support should be provided. There is a need for aftercare psychological support, especially for female childhood and AYA cancer survivors.

Psykososiaalinen selviytyminen nuorena sairastetun syövän jälkeen Tausta: Lapsena ja nuorena aikuisena syövän sairastaneiden määrän kasvaessa myös syövän aiheuttamien myöhäisvaikutusten ilmaantuvuus on lisääntynyt. Syövän sairastaneet tarvitsevat strukturoitua seurantaa, ja tehokkaiden tukimuotojen löytämiseksi tarvitaan lisää tutkimustietoa. Tutkimuksen tarkoitus ja metodit: Lapsena ja nuorena aikuisena syövän sairastaneiden psykososiaalisen selviytymisen tutkimiseksi, teimme neljä retrospektiivistä, kansallisiin rekisteritietoihin perustuvaa analyysiä. Ensimmäisessä osatyössä tutkittiin lapsena syövän sairastaneiden peruskoulun jälkeistä koulutusta ja sosiaalista selviytymistä. Seuraavassa osatyössä selvitettiin, ovatko muuttuneet terveystarkastusohjeet lisänneet lapsena syövän sairastaneiden sisäänottomääriä varuspalvelukseen, ja miten syövän sairastaneet suoriutuvat armeijan fyysisissä sekä kognitiivisissa testeissä. Kahdessa viimeisessä osatyössä tutkittiin lapsena ja nuorena aikuisena syövän sairastaneiden psykiatrista sairastuvuutta (HILMO-rekisterin psykiatriset diagnoositiedot) sekä masennuslääkeostotietoja (Lääkeostorekisteri) sisarusverrokkeihin nähden. Tulokset: Lapsena syövän sairastaneista suurempi osa jäi ilman peruskoulun jälkeistä koulutusta väestöverrokkeihin nähden. Sen sijaan lapsena syövän sairastaneilla ei havaittu suurentunutta riskiä työttömyyteen, mutta riski varhaiseen eläköitymiseen oli selvästi suurentunut kaikissa syöpäryhmissä. Lapsena sairastettu syöpä oli yhä merkittävä armeijaan pääsyn hylkäyssyy, mutta palvelukseen otetut syövän sairastaneet suoriutuivat pääosin hyvin armeijapalveluksessa. Riski aivojen orgaaniseen-/muistisairauteen havaittiin olevan suurentunut molemmissa tutkituissa ikäryhmissä (0-19 ja 20- 34-vuotiaana syöpädiagnoosin saaneet) ja naisilla havaittiin kaikissa ikäryhmissä enemmän mielialamuutoksia sekä masennuslääkeostoja kuin verrokeilla. Johtopäätökset: Lapsena aivokasvaimen tai leukemian/NHL:n sairastaneet saattavat tarvita tuen tarpeen kartoitusta kouluiässä, ja lapsena syövän sairastaneiden riittävän sosiaalinen tuen järjestäminen on tärkeää, jotta varhainen eläköityminen voidaan ehkäistä. Etenkin tytöt ja naiset tarvitsevat psykologista tukea sairastetun syövän jälkeen.